2015 International Conference on Clean Electrical Power (ICCEP) 2015
DOI: 10.1109/iccep.2015.7177620
|View full text |Cite
|
Sign up to set email alerts
|

Cascaded fuzzy logic based arc fault detection in photovoltaic applications

Abstract: Arc faults in photo-voltaic (PV) systems are dangerous events and can create huge damage. In order to decrease the number of these events, arc fault detectors are used. The advantages of the here presented detection algorithm are the relatively low computational demand and the ability to work with most standard analog-digital converter (ADC) contained in micro controllers.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(9 citation statements)
references
References 1 publication
0
8
0
Order By: Relevance
“…According to (16) and combined with the results of a large number of experiments, it is found that the training effect is best when the implied layer node points take 14. In addition, the studies [83] and [84] In [85] and [86], the authors used fuzzy logic system to detect the arc fault in the PV array. The accuracy of this method is increased up to 98.8%.…”
Section: ) Artificial Intelligence Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…According to (16) and combined with the results of a large number of experiments, it is found that the training effect is best when the implied layer node points take 14. In addition, the studies [83] and [84] In [85] and [86], the authors used fuzzy logic system to detect the arc fault in the PV array. The accuracy of this method is increased up to 98.8%.…”
Section: ) Artificial Intelligence Methodsmentioning
confidence: 99%
“…At present, numerous methods could detect the arc fault of PV systems: physical analysis (clustering method) [55][56][57][58], Fast Fourier Transform (frequency domain analysis) [59][60][61][62][63], time domain analysis [64][65][66][67], wavelet detection (multi-resolution analysis) [68][69][70][71][72][73][74][75][76][77], and Artificial Intelligence method (neural networks, support vector machines, fuzzy logic systems, etc.) [78][79][80][81][82][83][84][85][86].…”
Section: B Fault Diagnosismentioning
confidence: 99%
“…With the advancement of information technology, artificial intelligence (AI) methods have become popular and offer potential techniques in fault diagnosis in various areas such as high impedance fault detection in medium voltage networks [22], failure detection in electrical machines [23], and track circuit fault detection in railway systems [24]. Several recent studies have achieved promising results for DC series arc fault detection with AI-based methods, such as the combined use of a support vector machine (SVM) and wavelet packet decomposition for series arc fault detection [25], the use of a hidden Markov model (HMM) for obtaining the maximum likelihood of series arc faults for correctly detecting faults [26], and the use of a cascaded fuzzy logic system in a photovoltaic system for series arc fault detection [27]. Numerous features such as current variations and high-frequency energy are extracted, trained for series arc detection based on weighted least squares SVM algorithms [28].…”
Section: Introductionmentioning
confidence: 99%
“…In order to reconcile simplicity and efficiency, the strategy adopted in this work relies on an adaptive thresholding logic. The main part of the decision making is constituted by a Fuzzy logic processor largely used in recent years in fault diagnosis in photovoltaic and robotic systems [30][31][32][33] .…”
Section: Introductionmentioning
confidence: 99%